1993
DOI: 10.1073/pnas.90.23.11262
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the human alpha-globin gene cluster in transgenic mice.

Abstract: A 350-bp segment of DNA associated with an erythroid-specific DNase I-hypersensitive site (HS -40), upstream of the a-globin gene cluster, has been identified as the major tissue-specific regulator of the a-globin genes. However, this element does not direct copy number-dependent or developmentally stable expression of the human genes in transgenic mice. To determine whether additional upstream hypersensitive sites could provide more complete regulation of a gene expression we have studied 17 lines of transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 36 publications
5
39
1
1
Order By: Relevance
“…Analysis of -globin gene expression during development of the homozygous KO embryos showed a reduction in the / ϩ ␣ ratio from 50% at 9.5 days of gestation to 10% at 13.5 days to zero at 15.5 days (data not shown); this is similar to the pattern observed in normal animals, 7 suggesting that the loss of mHS Ϫ26 does not have a differential effect on the 2 genes.…”
Section: Removal Of the Floxed Neomycin Gene Partly Restores ␣-Globinsupporting
confidence: 65%
See 2 more Smart Citations
“…Analysis of -globin gene expression during development of the homozygous KO embryos showed a reduction in the / ϩ ␣ ratio from 50% at 9.5 days of gestation to 10% at 13.5 days to zero at 15.5 days (data not shown); this is similar to the pattern observed in normal animals, 7 suggesting that the loss of mHS Ϫ26 does not have a differential effect on the 2 genes.…”
Section: Removal Of the Floxed Neomycin Gene Partly Restores ␣-Globinsupporting
confidence: 65%
“…To address this question directly, we compared the expression in MEL cells of an mHS Ϫ26␣ construct (distinguished from the endogenous genes by using the coding sequence of the human ␣ gene) with that of an HS Ϫ40␣ construct studied previously. 7,24 The mHS Ϫ26␣ construct was cotransfected into adenine phosphoribosyltransferase (APRT)-negative MEL cells with an APRT plasmid and selected in histone acetyltransferase medium. Clones positive for mHS Ϫ26␣ were expanded and induced to terminal differentiation.…”
Section: Comparison Of the Expression Of Mhs ؊26␣ With Hs ؊40␣ Constrmentioning
confidence: 99%
See 1 more Smart Citation
“…Robertson et al (1995) described the silencing of expression of a construct containing an Escherichia coli lacZ gene under control of the human ~-globin HS-40 element in transgenic mice. It had been shown previously that HS-40 could not maintain highlevel copy number-dependent expression of the c~-globin gene throughout development as expression levels declined as development proceeded (Sharpe et al 1992(Sharpe et al , 1993. Histochemical staining for [3-gal showed that the lower expression levels seen late in development correlated with decreasing numbers of lacZ-expressing cells, and suggested that a decrease in the rate of transcription from individual promoters did not play a role.…”
Section: Modulation Of Gene Expressionmentioning
confidence: 88%
“…Lying 30-70 kb upstream of the α-globin genes, four highly conserved elements (multispecies conserved sequences, MCS-R1 to 4) corresponding to erythroid-specific DNase I hypersensitive sites (HS-48, HS-40, HS-33, HS-10, respectively) act as long-range regulatory elements of the α-like globin genes [4, reviewed in 5]. Several approaches like the analysis of interspecific hybrids [6] and stable transfectants [6,7], studies in transgenic mice [6,8] or in a humanized mouse model [9], provided evidence that the major regulatory element of this gene cluster in the human locus is MCS-R2 (which corresponds to HS-40). On their own, the other elements (MCS-R1, 3, 4) seem unable to induce substantial levels of α-globin gene expression.…”
Section: Introductionmentioning
confidence: 99%